Diagnosis dan Tata Laksana Hydroa Vacciniforme - Reshinta, Reisa; Rahmayunita, Githa; Rihatmadja, Rahadi; Astriningrum, Rinadewi (PT Kalbe Farma Tbk., 2024)
Hydroa vacciniforme (HV) is a rare photodermatoses with the most frequent onset in childhood. The exact pathogenesis of HV is still not known. This disease is a spectrum with almost similar clinical symptoms, but with a very different prognosis. Classic HV has the best prognosis, but affects the quality of life due to scar formation, while hydroa vacciniforme-like lymphoma (HVLL) is the variant with the worst prognosis. HV needs to be considered as a differential diagnosis, especially in childhood-onset photodermatoses. Classical HV must be distinguishes from hydroa vacciniforme-like lymphoproliferative disorders (HVLPD) because it is related to prognosis. There is still no consensus or guidelines on diagnosis and management for HV.